Multi target analysis of HeLa cells radiosensitivity - Khairuddin, Ili Zawani (Universiti Sains Malaysia, 2015)
The main objective of this study is to investigate the radiosensitivity of HeLa cells based on analysis using multi target model. Methods: The cell irradiations were performed using photon beam of energy 6 MV, 10 MV and electron beam of energy 6 MeV, 15 MeV. Samples were setup in full scatter condition using solid water phantom and bolus. Each sample was exposed to doses range from 1 to 10 Gy. Clonogenic assay were performed to obtain the cell survival curve data and the data were later analysis using Multi Target (MT) model. Analysis using Linear Quadratic (LQ) was also done for comparison. From the result, it shows that the survival curve for electron was steeper compared to photon beam. Therefore, HeLa cells were more radiosensitive to electron beam compared to photon beam. The MT model shows dominant reason of death cell due to multiple events cell killing which represents by Do. The value for Do for 6 MV, 10 MV, 6 MeV and 15 MeV were 2.42385, 3.39997, 2.42385, and 4022.75834 respectively. The MT model was found to be fitted better compare to LQ model for different energies and especially for high dose. HeLa cell is more radiosensitive toward photon beam than electron beam for MT Model while for the LQ model, cells were more radiosensitive to electron beam compare to photon beam. The Multi Target model describe the cell survive curve for high dose better than Linear Quadratic model.